Forecasting reference evapotranspiration under climate change scenario in Lake Finchaa Watershed, Ethiopia - Geleta, C. D.; Kannan, N. (International Journal of Agricultural Technology, 2021)
Forecasting the influences of climate change on hydro-climatic and agro-meteorological variables are continued and picked up extensively within the field of hydrology, climatology and agricultural water sciences. Reference Evapotranspiration (ETo) is an important agro-meteorological parameter for irrigation planning and management and highly susceptible to climate perturbation. The effects of climate change on the rate of ETo in Lake Finchaa watershed under of RCP4.5 and RCP8.5 (Representative Concentration Pathway) scenarios at the end of 2055 was investigated. The ETo under current climate condition was estimated by FAO-Penman Monteith (FAO-PM) and Hargreaves-Samani (H-S) models and used to establish the relationship between the models through regression analysis for prediction of future ETo. The signal of selected Regional Climate Models in the Coordinated Regional Climate Downscaling Experiment (RCM-CORDEX) was transferred to the observed temperature data using the change factor downscaling method. The ability of climate models in reproducing observation data was statistically evaluated and validated. The analysis result indicated that the rate of annual average ETo would be rising up to 4.42% at the end of 2055 due to the increase in temperature. The obtained result also showed that annual net rainfall deficit will increase by 77.93 mm per year in Lake Finchaa watershed for the same period. These may increase crop water requirement in the watershed and reduce the water retention and infiltration time into soil, which may lead to decline of water table level, that possibly lead to a reduction in the stream flow into Finchaa hydropower reservoir